2013
DOI: 10.1089/jpm.2012.0285
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Palliative Care Trial in Advanced COPD: A Feasibility Assessment (The COPD IMPACT Study)

Abstract: Providing home-based palliative care services for patients with advanced COPD is feasible but completing repeated questionnaires is impractical. Despite significant palliative supports, managing terminal symptoms exceeded caregivers' capacity to cope and forced hospital admission. Insights into systemic barriers and limitations of current palliative care service models can provide opportunities for local program innovation aimed at improving care for advanced COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 39 publications
1
83
1
1
Order By: Relevance
“…Failure to achieve increased QOL scores as a result of home-based palliative services have been reported elsewhere in the literature [39]. Perhaps stabilization of scores was in itself a positive outcome in this population who are experiencing declining health.…”
Section: Discussionmentioning
confidence: 77%
“…Failure to achieve increased QOL scores as a result of home-based palliative services have been reported elsewhere in the literature [39]. Perhaps stabilization of scores was in itself a positive outcome in this population who are experiencing declining health.…”
Section: Discussionmentioning
confidence: 77%
“…Another publication cited the patient's lack of understanding of their diagnosis and prognosis as being barriers to communication about COPD and palliative care [Gardiner et al 2010]. Horton and colleagues has done a good job of summarizing other common barriers to palliative care for those with COPD [Horton et al 2013]. These include the patient's limited comprehension of treatment options, failure to understand that COPD is a life-threatening disease, and limited ability to predict when supportive or palliative care services would be helpful and welcomed by the patient and family.…”
Section: Barriers To Palliative Carementioning
confidence: 99%
“…In a recent study of the feasibility of implementing a program of palliative care for patients with advanced COPD [29], we found that despite access to comprehensive medical support, which included individualized action plans and a er-hours physician response, Rocker & Cook. EOL Care for COPD some patients continued to turn repeatedly to the emergency room when symptoms escalated rapidly [29].…”
Section: Outreach For Patients With Advanced Copdmentioning
confidence: 99%
“…Success might be viewed through a di erent lens; whereby the dying begins at home but the death occurs in the hospital. Success might be considered in the light of averted visits to the emergency room, or through a short nal hospital admission without the intrusion of CPR as we have recently described [29].…”
Section: E Final Daysmentioning
confidence: 99%